What an entangled Web we weave: An information-centric approach to socio-technical systems - Luczak-Roesch, Markus; Tinati, Ramine; O'Hara, Kieron (PeerJ Preprints, 2017)
Motivated by the increasing amount of voices who ask for careful consideration of what context-rich data analysis methods can tell us about the activities of human collectives, we contribute an argumentation that employs a dialectic of literature on the philosophy of truth and science as well as analytical methods for the study of information diffusion, Web graphs and social networks in order to make a case for changing the current view to the actions of human collectives in the digital. We strengthen our meta argument by a case study about one particular method that breaks with the causality assumption that is inherent in many of today’s methods and allows to capture novel dimensions of complexity of information sharing from a macroscopic cross-system perspective. We discuss whether this kind of analysis may generically suit to underpin the field of socio-technical systems with a novel information-centric theory.
Keywords: Socio-technical Systems; Information Theory; Networks and Communities; Temporal Data Mining; Collective Intelligence; Augmented Intelligence; Social Machines; Citizen Science; Information Dynamics; Online Communities